Advances in Heterocatalysis by Nanomaterials - Ioannis V. Yentekakis; Wei Chu (Nanomaterials, 2020)
Heterogeneous catalysis played, plays, and will continue to play a major key role in industrial processes for the large-scale synthesis of commodity chemicals of global importance [1,2] and in catalytic systems that possess a critical role in energy generation [3−8] and environmental protection approaches [9−13] [...]